Effect of Self-Care Guideline on Quality of Life among Pregnant Women with Systemic Lupus Erythematosus - Saadia A. Mohamed; Nadia M. Fahmy; Sabah M. Mohamed; Nashwa A. Morshedy (Evidence-Based Nursing Research)
Context: Systemic Lupus Erythematosus (SLE) is a complex chronic autoimmune condition that represents a source of disability. In pregnant women, it can create a burden of the low quality of life and cause deleterious effects on maternal, fetal, and neonatal outcomes.